Perceived Values Of Mobile Banking In Malaysia - Muhammad, Fazil (2007)
This study examined consumer behaviour influencing mobile banking choice on the basis of consumer choice behaviour model. There are 5 perceived values; functional value, social value, emotional value, epistemic value and conditional value. This study is to find out the factors that influence the preference of consumers with regards to mobile banking. This study will provide assistance for management of financial institutions and service developers in order to attract consumers in competitive financial service environment.